A role for small secreted proteins (SSPs) in a saprophytic fungal lifestyle: Ligninolytic enzyme regulation in Pleurotus ostreatus - Feldman, Daria (Sci Rep, 2017)
Small secreted proteins (SSPs), along with lignocellulose degrading enzymes, are integral components of the secretome of Pleurotus ostreatus, a white rot fungus. In this study, we identified 3 genes (ssp1, 2 and 3) encoding proteins that are annotated as SSPs and that exhibited of ~4,500- fold expression, 24 hr following exposure to the toxic compound 5-hydroxymethylfurfural (HMF). Homologues to genes encoding these SSPs are present in the genomes of other basidiomycete fungi, however the role of SSPs is not yet understood. SSPs, aryl-alcohol oxidases (AAO) and the intracellular aryl-alcohol dehydrogenases (AAD) were also produced after exposure to other aryl-alcohols, known substrates and inducers of AAOs, and during idiophase (after the onset of secondary metabolism). A knockdown strain of ssp1 exhibited reduced production of AAO-and AAD-encoding genes after HMF exposure. Conversely, a strain overexpressing ssp1 exhibited elevated expression of genes encoding AAOs and ADD, resulting in a 3-fold increase in enzymatic activity of AAOs, as well as increased expression and protein abundance of versatile peroxidase 1, which directly degrades lignin. We propose that in addition to symbionts and pathogens, SSPs also have roles in saprophytes and function in P. ostreatus as components of the ligninolytic system.